The Mediating Role of Stress Between Workload, Work Environment, and Performance of Factory Workers - Kaban, Lila Maria; Jacksen (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2024)
Research Aim: This study investigates the influence of workload and work environment on employee performance, with work stress serving as the mediator Approach: The study employed a quantitative approach using SEM-PLS analysis. The sample included 75 factory workers selected through census sampling conducted from February to June 2023 at PT PSB, a manufacturing firm in Medan, North Sumatra Findings: Findings reveal that workload and work environment positively impact employee performance, mediated by work stress Theoretical Contribution/Originality: This research contributes to the literature by exploring work stress as a mediator in enhancing the understanding of employee performance within the manufacturing sector Policy Implication: Recommendations include PT PSB and similar companies prioritizing plant workers' stress levels, monitoring workload, and fostering a healthy workplace environment Research Limitation: The scope of the study was limited by the number of respondents and the factors considered in assessing employee productivity